Amorphous Electrically Actuating Submicron Fiber Waveguides. Issue 1 (21st September 2017) - Ishii, Yuya; Nobeshima, Taiki; Sakai, Heisuke; Omori, Keisho; Uemura, Sei; Fukuda, Mitsuo
Abstract: Amorphous electrically actuating submicron fiber waveguides are promising building blocks for creating novel opto‐electromechanical devices. In this study, waveguiding and electrically actuating properties of the waveguides composed of racemic poly(lactic acid) and a dye are investigated. The fibers have mean diameters of <0.4 µm, and each fiber demonstrates subwavelength waveguiding with a loss coefficient of 1.5 × 10 −4 –8.3 × 10 −4 µm −1 at 0.63 µm wavelength. Light propagates with a near‐light speed group velocity between wavelengths of 0.59 and 0.63 µm, where the fraction of power inside the core is 0.13–0.28. The fiber mat thicknesses change in response to both the polarity and the magnitude of an applied voltage, similar to the inverse‐piezoelectric effect. The estimated values for both the apparent piezoelectric constant (29 000 × 10 −12 m V −1 ) and Young's modulus (1.5 kPa) indicate a high degree of electricity actuation and a soft mat. Extremely small, soft, and electrically actuating waveguides can produce novel opto‐electromechanical devices. Abstract : The properties of novel electrically actuating and waveguiding amorphous polymer submicron fibers are investigated in detail. These fibers guide light at subwavelength diameters with a group velocity greater than 0.71 c 0 . The fiber mat also demonstrates electrical actuation with a high apparent piezoelectric constant of ≈29 000 × 10 −12 m V −1 . Extremely small and functional waveguides can be used to produce novel opto‐electromechanical devices.